(untitled) (Majalah Ekonomi, 2022)
This article criticizes the development of accounting theory and accounting research. This theory is generally developed more slowly than the practice of double-entry bookkeeping. According to its development, accounting practices are influenced by environmental factors such as social, economic, political. Therefore, the structure and practice of accounting will be different in each country, and in accounting research can find simple non-formal investigations. For example, the use of deductive and inductive. This approach resulted in the development of theory. Descriptive/positive theory. More accounting theories and research have been developed in various fields and concepts such as economics, finance, psychology and sociology. This can help to increase the speed of accounting in the future that will come.